Quantitative evaluation of antioxidant activities of native plants of the Alto Oeste Potiguar Region / RN (Research, Society and Development, 2020)
In Brazil, popular knowledge about medicinal plants is the reason for several investigations involving various plant species. Among the studies conducted with plant extracts, there is a special interest in antioxidant activity, which acts by inhibiting and/or decreasing the effects triggered by free radicals and oxidizing compounds. From this perspective, the present work evaluated the antioxidant action of ethanolic extracts species: Pereiro (Aspidosperma pyrifolium Mart), Juazeiro (Ziziphus joazeiro Mart), Catingueira (Caesalpinia pyramidalis Tui), Black Jurema (Mimosa tenuiflora Willd) and Ameixa Selvagem (Ximenia americana L.) natives to the Alto Oeste Potiguar region of Rio Grande do Norte. The leaves and stems were collected at Barro Vermelho site, in São Francisco do Oeste (RN), to obtain the extracts. They were then subjected to antioxidant activity tests using the DPPH free radical. All samples analyzed showed a good percentage of antioxidant activity in their different concentrations, highlighting the EEFA, which had the highest percentage of antioxidant activity at the lowest concentration. Thus, it is suggested that from these data, these species may have medicinal purpose as popular knowledge.